Worldwide Incidence and Prevalence of Neuromyelitis Optica: A Systematic Review. (12th January 2021) - Papp, Viktoria; Magyari, Melinda; Aktas, Orhan; Berger, Thomas; Broadley, Simon A.; Cabre, Philippe; Jacob, Anu; Kira, Jun-ichi; Leite, Maria Isabel; Marignier, Romain; Miyamoto, Katsuichi; Palace, Jacqueline; et al.
Abstract : Objective: Since the last epidemiologic review of neuromyelitis optica/neuromyelitis optica spectrum disorder (NMO/NMOSD), 22 additional studies have been conducted. We systematically review the worldwide prevalence, incidence, and basic demographic characteristics of NMOSD and provide a critical overview of studies. Methods: PubMed, Ovid MEDLINE, and Embase using Medical Subject Headings and keyword search terms and reference lists of retrieved articles were searched from 1999 until August 2019. We collected data on the country; region; methods of case assessment and aquaporin-4 antibody (AQP4-Ab) test; study period; limitations; incidence (per 100, 000 person-years); prevalence (per 100, 000 persons); and age-, sex-, and ethnic group–specific incidence or prevalence. Results: We identified 33 relevant articles. The results indicated the highest estimates of incidence and prevalence of NMOSD in Afro-Caribbean region (0.73/100 000 person-years [95% CI: 0.45–1.01] and 10/100 000 persons [95% CI: 6.8–13.2]). The lowest incidence and prevalence of NMOSD were found in Australia and New Zealand (0.037/100 000 person-years [95% CI: 0.036–0.038] and 0.7/100, 000 persons [95% CI: 0.66–0.74]). There was prominent female predominance in adults and the AQP4-Ab–seropositive subpopulation. The incidence and prevalence peaked in middle-aged adults. African ethnicity had the highest incidence and prevalence of NMOSD, whereas White ethnicity had the lowest. No remarkable trend of incidence was described over time. Conclusion: NMOSD is a rare disease worldwide. Variations in prevalence and incidence have been described among different geographic areas and ethnicities. These are only partially explained by different study methods and NMO/NMOSD definitions, highlighting the need for specifically designed epidemiologic studies to identify genetic effects and etiologic factors.